THE USE OF GENERATING INTERACTION BETWEEN SCHEMATA AND TEXT (GIST) STRATEGY TOWARDS STUDENTS’ READING COMPREHENSION - Venny Octavia; Eka Wilany (Universitas Riau Kepulauan, 2018)
As a foreign language learner, Indonesian students are not easy to comprehend the text in English; the students have to understand implicit and explicit meaning in the text. It is also not easy for them to get the implicit meaning in interpreting the meaning and purpose of an English text. Strategy in teaching English specifically reading comprehension can affect the student achievement in learning. One of the teaching strategies that is considered useful is Generating Interaction between Schemata and Text (GIST) strategy that provides an opportunity for students to identify important vocabulary and synthesize important pieces of information into summary statement to show the gist of the reading. The research was conducted by using experimental design in quantitative approach. It was conducted to know whether there was any significant effect of Generating Interaction between Schemata and Text (GIST) strategy toward students’ reading comprehension. The instrument used to assess the students reading comprehension was reading test that distributed to the students in the experimental and control class. The sample of the research was 73 students, from 2 classes. The hypotheses was calculated by using t-test in which the analysis result obtained tcount =7.63 ttable = 1.99 with α = 0,05, dk = n1+n2-2 (37+35-2) = 70. It means that there was significant effect of GIST Generating Interaction between Schemata and Text (GIST) strategy toward students’ reading comprehension.